2010
DOI: 10.1073/pnas.1006538107
|View full text |Cite
|
Sign up to set email alerts
|

Resolving postglacial phylogeography using high-throughput sequencing

Abstract: The distinction between model and nonmodel organisms is becoming increasingly blurred. High-throughput, second-generation sequencing approaches are being applied to organisms based on their interesting ecological, physiological, developmental, or evolutionary properties and not on the depth of genetic information available for them. Here, we illustrate this point using a low-cost, efficient technique to determine the fine-scale phylogenetic relationships among recently diverged populations in a species. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
374
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(385 citation statements)
references
References 37 publications
(36 reference statements)
1
374
0
4
Order By: Relevance
“…This approach meets the demands of population geneticists, providing many loci for potentially large numbers of individuals, while securing the cost-benefit of NGS by obtaining large amounts of data per lane of sequencing. This is exemplified in a study by Emerson et al (2010) where 3741 SNPs fixed within and variable among populations were identified, for a total of 126 individuals, in two lanes of an ILLUMINA GAIIX sequencer.…”
Section: Combined Approaches For Marker Detection and Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach meets the demands of population geneticists, providing many loci for potentially large numbers of individuals, while securing the cost-benefit of NGS by obtaining large amounts of data per lane of sequencing. This is exemplified in a study by Emerson et al (2010) where 3741 SNPs fixed within and variable among populations were identified, for a total of 126 individuals, in two lanes of an ILLUMINA GAIIX sequencer.…”
Section: Combined Approaches For Marker Detection and Applicationmentioning
confidence: 99%
“…RAD markers are short sequences of DNA adjacent to a restriction enzyme recognition site, in which SNPs are compared between individuals (full method in Miller et al, 2007b, and summarized in Figure 2c). This technique has been used in various organisms such as Drosophila (Miller et al, 2007b), Neurospora (Baird et al, 2008), the pitcher plant mosquito (Emerson et al, 2010), zebrafish (Miller et al, 2007a), the three spine stickleback (Miller et al, 2007b), trout (Hohenlohe et al, 2011) and barley (Chutimanitsakun et al, 2011). This approach sequences a subset of the genome to reduce costs and uses barcodes for individual samples to allow bulk sequencing.…”
Section: Combined Approaches For Marker Detection and Applicationmentioning
confidence: 99%
“…Next generation sequencing techniques can provide the quantity of data necessary to evaluate these alternatives and to resolve recalcitrant clades. Recent phylogenetic studies employing restriction-site associated DNA (RAD) sequence data (Baird et al 2008;Emerson et al 2010;Wagner et al 2012;Eaton and Ree 2013) suggest that this technique holds promise for Cecropia. Rubin et al (2012) found that RAD sequencing for phylogenetic analysis worked best for diploid species that diverged relatively recently (<60 Mya) which is the case for Cecropia.…”
Section: ] Treiber Et Al: Phylogeny Of the Cecropieae (Urticaceae)mentioning
confidence: 99%
“…Among populations [22,36,37], crosses between the southern (ancestral) and northern (derived) populations [18,19] consistently revealed genetic differences in photoperiodic response involving epistasis but varied among crosses in the components of digenic epistasis (additive  additive, additive  dominance, dominance  dominance). A cross between the AL population used in this study and a Florida population at the same latitude involved dominance, maternal additive, maternal dominance and epistatic effects.…”
Section: Discussion (A)mentioning
confidence: 99%